Italian Students as a Political Actor. The Policy Impact of the Recent Student Mobilizations in the Field of Higher Education - Cini, Lorenzo (PARTECIPAZIONE E CONFLITTO, 2017)
After decades of political passivity, Italian students have massively mobilized in the years 2008 and 2010 to protest the implementation of two political measures fostering a neoliberal conception of higher education. More notably, the casus belli of these mobilizations concerned the implementation of a financial measure cutting public funding for higher education in 2008, accompanied by a New Public Management (NPM) reform of university governance in 2010. Despite a high rate of participation, none of the two mobilizations managed to alter the political course of events. The Italian government approved and implemented the two measures and the Italian student movement lost this political battle. In short, recent student mobilizations failed to produce any policy impact on the Italian field of higher education. Why was this the case? My argument is that organizationally and politically fragmented protests are not able to influence policy issues that have a low public relevance, especially in periods of economic crisis and political austerity. I contend that this was precisely the case of the Italian student protests of 2008 and 2010.